Antibacterial effectivity of coffee bean extract and instant coffee (spray drying) against porphyromonas gingivalis - Tantin Ermawati; Nazilaturrohmah; Achmad Gunadi; Dessy Rachmawaty (Journal of Dentomaxillofacial Science, 2022)
Objective:This study aims to determine effectiveness of antibacterial of Coffee Bean Extract and Instant Coffee (Spray Drying) against Porphyromonas gingivalis. Material and Methods: Dilution of coffee bean extract and instant coffee (spray drying) using the serial dilution method into several predetermined concentrations. Antibacterial activity using the disc diffusion method. The zone of inhibition was measured using a caliper Results: The results showed that the inhibition zone of coffee bean extract was greater than that of instant coffee (spray drying) against Porphyromonas gingivalis. Conclusion: The antibacterial of the coffee bean extract is more effective than instant coffee (spray drying) against Porphyromonas gingivalis